Enhancement of Cytomegalovirus-Specific Cytokine Production after Modulation of the Costimulation in Kidney Transplant Patients - Theresa Dornieden; Benjamin Wilde; Johannes Korth; Kai Werner; Peter A. Horn; Oliver Witzke; Monika Lindemann (Journal of Immunology Research)
Kidney transplantation is the therapy of choice for patients with end stage renal disease. Due to immunosuppressive treatment, patients are at risk for opportunistic infections. Cytomegalovirus (CMV) reactivation is highly relevant in kidney transplant recipients because it occurs—depending on the serological constellation of the donor and recipient—in more than half of the patients and influences patient outcome. Patients with CMV reactivation show decreased allograft and overall survival. Previous studies could demonstrate that transplant patients often show weak CMV-specific immunity. Besides immunosuppressive treatment, additional mechanisms may reduce CMV-specific immunocompetence such as enhanced negative costimulation. Hence, the aim of this study was to investigate if the function of CMV-specific cells of kidney transplant recipients could be restored by a modulation of costimulatory molecules. To address this question, lymphocytes of kidney transplant patients were stimulated with CMV-specific antigens and incubated with programmed death-ligand 1 (PD-L1), programmed cell death protein 1 (PD-1), or B- and T-lymphocyte attenuator (BTLA) antibodies. Afterwards, the IFN-γ, IL-21, and IL-17A production was measured by the ELISpot assay. It could be shown that a blockade of the ligand PD-L1 resulted in an increased CMV-specific IFN-γ, IL-21, and IL-17A secretion. The blockade of the receptor PD-1 distinctly enhanced the production of IL-21. BTLA antibodies, however, led only to a marginal increase of CMV-specific IFN-γ and of IL-21 production. Experiments in healthy controls could confirm the results of the kidney transplant recipients. Furthermore, they could demonstrate that treatment with the immunosuppressive drug tacrolimus resulted in decreased CMV-specific IFN-γ and of IL-21 production. Thus, our study could show for the first time that the blockade of the PD-L1/PD-1 pathway also modulates CMV-specific Th21 and Th17 cell function in kidney transplant recipients. Further studies are mandatory to clarify the role of Th21 and Th17 cells in CMV control of these patients.